Deciphering neo-sex and B chromosome evolution by the draft genome of Drosophila albomicans - Zhou, Qi (BioMed Central, 2012)
BACKGROUND: Drosophila albomicans is a unique model organism for studying both sex chromosome and B chromosome evolution. A pair of its autosomes comprising roughly 40% of the whole genome has fused to the ancient X and Y chromosomes only about 0.12 million years ago, thereby creating the youngest and most gene-rich neo-sex system reported to date. This species also possesses recently derived B chromosomes that show non-Mendelian inheritance and significantly influence fertility. METHODS: We sequenced male flies with B chromosomes at 124.5-fold genome coverage using next-generation sequencing. To characterize neo-Y specific changes and B chromosome sequences, we also sequenced inbred female flies derived from the same strain but without B's at 28.5-fold. RESULTS: We assembled a female genome and placed 53% of the sequence and 85% of the annotated proteins into specific chromosomes, by comparison with the 12 Drosophila genomes. Despite its very recent origin, the non-recombining neo-Y chromosome shows various signs of degeneration, including a significant enrichment of non-functional genes compared to the neo-X, and an excess of tandem duplications relative to other chromosomes. We also characterized a B-chromosome linked scaffold that contains an actively transcribed unit and shows sequence similarity to the subcentromeric regions of both the ancient X and the neo-X chromosome. CONCLUSIONS: Our results provide novel insights into the very early stages of sex chromosome evolution and B chromosome origination, and suggest an unprecedented connection between the births of these two systems in D. albomicans.